Women's education in developing countries : barriers, benefits, and policies - King, Elizabeth M.; Hill, M. Anne. (Baltimore : Published for the World Bank [by] the Johns Hopkins University Press, 1993)
The book brings together information on women's education from a variety of data bases, examines the relationship between women's education and development, reviews research results for each developing region, identifies gaps in current knowledge, and discusses problems of methodology.
"World Bank book."
Includes bibliographical references and indexes.
osc 02/09/16
Loans
Keywords: Women - education - developing countries; Women - education - economic aspects; Educational equalization